Discovering Oboé - Castanheira, Adriana (2020)
The purpose of this workshop is to disseminate the oboe and encourage study, by creating an environment of cooperation between teachers, professionals and students. This presentation will be presented with a theoretical part and a practical part. The methodology used in this intervention will go through the following moments: i) we will start with a brief characterization of the instrument, giving a brief summary of its origin, history, family; features; (ii) a brief demonstration of the process leading to the manufacture of reeds, the lashing and scraping of the reed; iii) in a third stage will be held the practical part, in which two students (1st and 5th grades of Basic Education of the Regional Conservatory of Music of Vila Real of the class of teacher Adriana Castanheira) will interpret two pieces, with a degree of differentiated difficulty , in order to show that the so infamous, how unknown instrument, despite the difficulty of playing it, can be touched by all: the singularity of the instrument that serves as tuning for the orchestras, deserves this apology.